The School of Alexandria and the Emergence of Neo-Platonism - Qasibat, Mostafa Mohammed ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2015)
This study examines the emergence and development of the Alexandrian School of Philosophy, widely considered the birthplace of Neoplatonism—a major philosophical movement that emerged from the convergence of Greek rational thought and Eastern spiritual traditions. The Alexandrian School played a pivotal role in shaping Hellenistic philosophy, blending Neo-Pythagorean, Jewish, and skeptical elements with a reinterpreted form of Platonism. The paper explores two conceptual challenges arising from the term "School of Alexandria": first, whether it is more accurate to refer to this philosophical tradition by its geographic origin or by the term Neoplatonism, which has gained more traction in Western philosophical literature; and second, the confusion between the philosophical school and the Alexandrian Museum or Library, which has led some to downplay its philosophical significance. Through key thematic sections, the study addresses the intellectual dynamics, methodology, and major figures of the school—such as Ammonius Saccas, Plotinus, and Proclus—as well as the Eastern influences that helped shape Neoplatonic thought. Adopting a historical-analytical-critical approach, the research highlights the Alexandrian School as a central meeting point for ancient civilizations and a foundational space for the synthesis of diverse philosophical traditions.